2021
DOI: 10.1186/s12866-021-02239-6
|View full text |Cite
|
Sign up to set email alerts
|

SpoVG is an important regulator of sporulation and affects biofilm formation by regulating Spo0A transcription in Bacillus cereus 0–9

Abstract: Background Bacillus cereus 0–9, a Gram-positive, endospore-forming bacterium isolated from healthy wheat roots in our previous research, is considered to be an effective biocontrol strain against several soil-borne plant diseases. SpoVG, a regulator that is broadly conserved among many Gram-positive bacteria, may help this organism coordinate environmental growth and virulence to survive. This study aimed to explore the multiple functions of SpoVG in B. cereus 0–9. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 45 publications
0
11
0
3
Order By: Relevance
“…2B) . FM 4-64 is also used to stain the membranes of sporulating cells of B. subtilis and B. cereus; however, it cannot stain the forespore at stage VI and later (Pogliano et al, 1999;Huang et al, 2021) . Hoechst 33342 facilitated the visualization of chromosomal DNA in B. cereus NBRC 3836, most of the cells observed were vegetative cells (Fig.…”
Section: Morphological Change During the Sporulation In B Cereus Atcc...mentioning
confidence: 99%
“…2B) . FM 4-64 is also used to stain the membranes of sporulating cells of B. subtilis and B. cereus; however, it cannot stain the forespore at stage VI and later (Pogliano et al, 1999;Huang et al, 2021) . Hoechst 33342 facilitated the visualization of chromosomal DNA in B. cereus NBRC 3836, most of the cells observed were vegetative cells (Fig.…”
Section: Morphological Change During the Sporulation In B Cereus Atcc...mentioning
confidence: 99%
“…For example, experiments using mutagenesis, heterologous expression, and transcription profiling indicated that B. cereus AR156 harbors a highly similar genetic circuit ( Bcspo0A - BcsinI - BcsinR ) [ 49 ]. A more recent study explored the multiple functions of SpoVG, another important sporulation regulator, in B. cereus 0–9 [ 50 ]. In B. subtilis , SpoVG is involved in sporulation via an unexplored mechanism, while studies on B. cereus 0–9 revealed that SpoVG controls biofilm formation by activating the transcription of Spo0A.…”
Section: Global Analysis Of Biofilm Developmentmentioning
confidence: 99%
“…In B. subtilis , SpoVG is involved in sporulation via an unexplored mechanism, while studies on B. cereus 0–9 revealed that SpoVG controls biofilm formation by activating the transcription of Spo0A. Furthermore, SpoVG was also reported to influence both AbrB and SinI/SinR networks, and therefore biofilm development [ 50 ]. Thus, it was speculated that SpoVG is positioned upstream of Spo0A in the regulatory pathway, which expanded our knowledge of the spo0A - sinI - sinR genetic circuit in B. cereus .…”
Section: Global Analysis Of Biofilm Developmentmentioning
confidence: 99%
“…One putative mediator of σ B activity could be SpoVG (aka BarB in S. epidermidis ), a DNA/RNA-binding protein that is highly conserved in eubacteria [ 30 ]. SpoVG is a known regulator of virulence in a number of pathogenic firmicutes such as Bacillus cereus [ 31 ], Listeria monocytogenes [ 32 ], and S. aureus [ 33 , 34 , 35 ]. The regulatory protein is also reported to affect biofilm formation in B. cereus [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…SpoVG is a known regulator of virulence in a number of pathogenic firmicutes such as Bacillus cereus [ 31 ], Listeria monocytogenes [ 32 ], and S. aureus [ 33 , 34 , 35 ]. The regulatory protein is also reported to affect biofilm formation in B. cereus [ 31 ]. Given that σ B controls the transcription of SpoVG in S. aureus [ 33 ] and that activity of SpoVG is enhanced by Stk1-mediated phosphorylation in the latter species [ 36 ], we wondered whether and how SpoVG might affect biofilm formation and ica transcription in S. epidermidis .…”
Section: Introductionmentioning
confidence: 99%